Instructional design and course delivery as meta-ensemble : Improvisatory responses to COVID constraints in tertiary music ensemble assessments. - Yeo, Narelle; Fuller, Brad; Kenway, Simon (Journal of University Teaching & Learning Practice v.20 n.3 https://doi.org/10.53761/1.20.3.05, 2023)
This research considers the synchronous creation of a faculty meta-ensemble emergent in the pivot to online music ensembles in 2021. The unit of study outline for Music Ensemble Performance mandates live ensembles in a Kolb-inspired experiential learning model, seemingly impossible to achieve in a pandemic. Eric Ries advocates for necessary change in strategy, where required, without a change in vision. This was also mandated by the published unit of study outline, which limited change possibilities. In this auto-ethnographic case study, faculty created their own co-teaching meta-ensemble to model collaborative musical behaviours. Keller and Appel (2010) note the importance of live embodiment of collaborative music making for sound synchronicity through shared gestures. It was initially unclear how this could be achieved through exclusive online learning. A necessary course pivot during the pandemic showed 1. Ensemble music making is a unique complex adaptive culture, also possible to create in an online environment; and 2. Faculty can model behaviours and structures that are able to mirror ensemble course outcomes. Instructional designers can also embody the courses they teach. This has implications for other teaching and learning contexts. [Author abstract]